The Number Of Lactobacillus acidophilus After Using Chlorhexidine 2%, Laser Diode (405 nm), And Combination Of Chlorhexidine 2% With Laser Diode (405 nm) - Sri Kunarti; Sukaton Sukaton; Nadya Nathania (Universitas Airlangga, 2019)
Background: Lactobacillus acidophilus is gram-positive bacteria that produces acids from carbohydrates and causing dental caries. Caries treatment is done by the cavitation of teeth which is preceded by cavity disinfection. The purpose of cavity disinfection is to kill microorganisms and reduce the risk of new carious lesions. Bacterial elimination can be done using chlorhexidine and laser. Chlorhexidine is widely used for cleaning cavities but cannot remove biofilms, tissue debris and has limited elimination of bacteria in the dentinal tubules. Another way to eliminate bacteria is using Photodynamic Therapy (PDT) which consists of photosensitizer and laser. Until now there has not been a single ingredient that is considered to cleanse the cavity thoroughly. There has been no research yet that examine the number of Lactobacillus acidophilus after using chlorhexidine 2%, laser diode (405 nm), and combination of 2% chlorhexidine with laser diode (405 nm). Objective: To compare the decreasing number of living Lactobacillus acidophilus after using chlorhexidine 2%, laser diode (405 nm), and combination of chlorhexidine 2% with laser diode (405 nm). Methods: A total of 24 samples of Lactobacillus acidophilus were divided into 4 groups: (I) chlorhexidine 2%, (II) chlorophyll photosensitizer and 75 seconds irradiation, (III) combination of chlorhexidine2%, chlorophyll photosensitizer, and 75 seconds irradiation. After treatment, the sample was incubated 48 hours and the colony count was calculated for each group. Results of the analysis were carried out by ANOVA and Tukey HSD tests with p <0.05. Results: The average number of group colonies (I) was 35.33 CFU/ml, (II) 16.83 CFU/ml, (III) 9.5 CFU/ml, (IV) 123.33 CFU/ml. Conclusion: The combination of 2% chlorhexidine with diode laser (405 nm) gives the least amount of living Lactobacillus acidophilus bacteria compared with the administration of 2% chlorhexidine and laser diode (405 nm).